Effect of novel human milk oligosaccharides-based human milk fortifier containing lactoferrin, docosahexaenoic acid, and arachidonic acid on the growth of preterm infants with birth weight of 700–1800 g - Sengupta, Amitava; Lal, Ajay; Bhayana, Harsh (Indian Journal of Child Health, 2024)
Background: Premature infants with low birth weight are at risk of growth failure and neurodevelopmental impairment. Human milk oligosaccharides (HMOs) are bioactive components of human milk that may enhance growth and development. The novel HMO-based human milk fortifier (HMoF), which also contains lactoferrin, docosahexaenoic acid (DHA), and arachidonic acid (ARA), can help provide a safer nutritional option for the growth of premature infants. Materials and Methods: We conducted a non-comparative observational study using data from multiple centers that used novel HMO-based HMF (HMoF) in premature infants (n=14) with birth weights of 700–1800 g. The primary outcome of the study was to assess tolerability (in terms of feed tolerance), and secondary outcomes included growth outcomes defined by weight, length, and head circumference during the stay in the NICU and at discharge. Results: A cohort consisting of 14 infants with a mean gestational age of 30.21±2.04 weeks and a birth weight of 1246.36±39.98 g comprised the study. During the study period, incidences of feed interruptions due to feed intolerability were nil, and no infant presented with any signs of adverse effects. The novel HMO-based HMF (HMoF)-fed infant cohort had a mean weight gain of 21.89±5.23 g/day, a mean length gain of 1.01±0.48 cm/week, and mean head circumference gain of 0.89±0.32 cm/week. The mean growth velocity recorded was 16.03±1.73 g/kg/day. Conclusions: Novel HMO-based HMF (HMoF) containing lactoferrin, DHA, and ARA demonstrated acceptable feed tolerance and weight gain without any clinically significant adverse effects. Data indicates that the novel HMoF containing lactoferrin, DHA, and ARA is a safe option for supporting the growth of preterm babies. However, further studies are needed to compare novel HMO-based HMF (HMoF) with standard HMF in a randomized controlled trial.